2009
DOI: 10.1093/pcp/pcp150
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a Brassica rapa NGATHA Gene in Arabidopsis thaliana Negatively Affects Cell Proliferation During Lateral Organ and Root Growth

Abstract: In an effort to elucidate biological functions of transcription factors of Brassica rapa L. (ssp. pekinensis), an NGATHA homolog, BrNGA1, that belongs to the B3-type transcription factor superfamily was identified and expressed in Arabidopsis thaliana under the control of the cauliflower mosaic virus (CaMV) 35S promoter. Arabidopsis plants overexpressing BrNGA1, named BrNGA1ox, displayed markedly reduced organ growth compared with the wild type: lateral organs, such as leaves, flowers and cotyledons, were smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 50 publications
2
21
0
2
Order By: Relevance
“…Ten micrograms of total RNAs were subjected to Northern blot analysis, as described by Kwon et al (2009). To prepare gene-specific DNA probes, genomic DNA regions corresponding to the 3′ half and untranslated region of each AtNGA cDNA were amplified by PCR (for primer sequence information, see Online Resource 1).…”
Section: Northern Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Ten micrograms of total RNAs were subjected to Northern blot analysis, as described by Kwon et al (2009). To prepare gene-specific DNA probes, genomic DNA regions corresponding to the 3′ half and untranslated region of each AtNGA cDNA were amplified by PCR (for primer sequence information, see Online Resource 1).…”
Section: Northern Blot Analysismentioning
confidence: 99%
“…Although Alvarez et al (2009) showed that bigger petals of the nga1-1 mutant resulted from an increase in cell numbers, it remains to be resolved in more detail what exact roles the AtNGA genes play in regulating the cell proliferation activity of lateral organs. In the meantime, we previously demonstrated that Arabidopsis plants overexpressing a Brassica rapa NGA gene (BrNGA1) displayed a remarkable reduction in cell numbers and thus small, narrow lateral organs, leading to the hypothesis that BrNGA1 may also act as a negative regulator of cell proliferation in B. rapa (Kwon et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Five-day-old wild-type and transgenic Arabidopsis leaves were cleared in a chloral hydrate solution as described previously (Kwon et al 2009). The leaf cell layers were visualized by light-field microscopy (BX51 fluorescence microscope, Olympus, Japan).…”
Section: Microscopymentioning
confidence: 99%
“…Arabidopsis overexpressors of BrNGA1 (BrNGA1ox) are prepared as described previously (Kwon et al 2009). The CKX2ox seeds were kindly provided by Dr. Thomas Schmülling.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Recently, we have analyzed Arabidopsis overexpressors of a Brassica rapa NGATHA gene, BrNGA1, which encodes a B3-type transcription factor (Kwon et al 2009). Our study demonstrated that the BrNGA1 transcription factor may be involved in negative regulation of cell proliferation during lateral organ and root growth.…”
Section: Introductionmentioning
confidence: 99%